Usain Bolt: Running with primary display of maximum power under competitive conditions - Mironenko, I. N.; Mirzoev, O. M. (Theory and Practice of Physical Culture, 2017)
Abstract: The phenomenal sports results and achievements of Jamaican sprinter, multiple world record-holder, world champion and Olympic champion U. Bolt will attract the attention of specialists in different spheres for many years to come, as this athlete is alone in his ability to effectively and consistently display maximum anaerobic power in extreme conditions for a long time. A multi-year research on the kinematic parameters of the athlete`s technical skills in the 100 m distance run, conducted during various competitions, as presented in the current paper, has enabled to detect the peculiarities of organization of biomechanical characteristics, as well as find the ways to improve the efficiency of motor actions carried out with maximum power.